2019
DOI: 10.1186/s12936-019-2766-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Plasmodium species and assessment of performance of diagnostic tools used during a malaria survey in Southern and Western Provinces of Zambia

Abstract: Background Zambia continues to make strides in reducing malaria burden through the use of proven malaria interventions and has recently pledged to eliminate malaria by 2021. Case management services have been scaled up at community level with rapid diagnostic tests (RDTs) providing antigen-based detection of falciparum malaria only. Key to national malaria elimination goals is the ability to identify, treat and eliminate all Plasmodium species. This study sought to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
7
29
0
Order By: Relevance
“…Zambia, P. falciparum dominates the landscape with ∼98% of all infections, P. malariae is consistently found in 2-4% of all infections, while P. ovale is rarely observed, and P. vivax essentially absent. [27][28][29][30] This study broadly confirmed these observations, with P. falciparum representing 97.5% of all infections and small numbers of infections from P. ovale and P. malariae (Table 4). It is unclear at this stage why a large proportion of non-P. falciparum infections could not be resolved to the species level.…”
Section: Discussionsupporting
confidence: 72%
“…Zambia, P. falciparum dominates the landscape with ∼98% of all infections, P. malariae is consistently found in 2-4% of all infections, while P. ovale is rarely observed, and P. vivax essentially absent. [27][28][29][30] This study broadly confirmed these observations, with P. falciparum representing 97.5% of all infections and small numbers of infections from P. ovale and P. malariae (Table 4). It is unclear at this stage why a large proportion of non-P. falciparum infections could not be resolved to the species level.…”
Section: Discussionsupporting
confidence: 72%
“…This could understandably justify the focus on P. falciparum malaria diagnosis in Zambia over the other species. With regards to other species, studies have shown that P. malariae is characterized by chronic infections, while P. ovale has dormant hypnozoites stages, which may explain the lower haemolysis rate [ 54 ]. In spite of the varying pathogenesis of malaria in infections with the different species, these infections still demand attention.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 94 samples with discordant results between microscopy and RDTs were selected for further molecular characterization. Genomic DNA was extracted from DBS of these 94 samples using QIAamp DNA Mini Kits (Hilden, Germany) using manufacturers’ protocol and screened for parasite DNA using the multiplex photo-induced electron transfer PCR (PET-PCR) assay as previously described [ 42 45 ]. PCR for pfhrp2 and pfhrp3 genotyping was performed as described previously [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%